Electro-optical tuning of plasmon-driven double reduction interface catalysis. (June 2018) - Lin, Weihua; Ren, Xin; Cui, Lin; Zong, Huan; Sun, Mengtao
Graphical abstract: Highlights: We experimentally report plasmon-driven double reduction reactions in electrochemical environments. One of nitro group of two PDNBs was reduced to azo (NN) group, and the other two nitro groups of the azoic compound were reduced to amino groups. The Raman spectra of p-phenylenediamine, 4, 4′-diaminoazobenzene, 4, 4′-dinitroazobenzene are also measured. Our works can provide deeper understanding of plasmon-driven multiple-step surface catalytic reactions. Abstract: In this paper, we experimentally report plasmon-driven double reduction reactions in electrochemical environments, where the p-dinitrobenzene was reduced to DAAB via double reduction reactions. One of nitro group of two PDNBs was reduced to azo (NN) group, and the other two nitro groups of the azoic compound were reduced to amino groups. To provide confirm experimental evidence, the Raman spectra of p-phenylenediamine, 4, 4′-diaminoazobenzene, 4, 4′-dinitroazobenzene are also measured. Our works can provide deeper understanding of plasmon-driven multiple-step surface catalytic reactions.